2003
DOI: 10.2176/nmc.43.573
|View full text |Cite
|
Sign up to set email alerts
|

Technetium-99m Sestamibi Single Photon Emission Computed Tomography Findings Correlated With P-glycoprotein Expression, Encoded by the Multidrug Resistance Gene-1 Messenger Ribonucleic Acid, in Intracranial Meningiomas

Abstract: The present study evaluated whether technetium-99m sestamibi ( 99m Tc-MIBI) single photon emission computed tomography (SPECT) characteristics of intracranial meningioma are correlated with the histological malignancy, proliferative potential, and P-glycoprotein (Pgp) expression, encoded by the multidrug resistance gene-1 (MDR-1) messenger ribonucleic acid (mRNA). Twenty-one patients with intracranial meningiomas, including 17 benign and four nonbenign meningiomas, underwent 99m Tc-MIBI SPECT imaging at 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
3
9
0
Order By: Relevance
“…This strongly associates with pituitary adenomas. [781021] Our study supports this data and suggests a simple semiquantitative index to diagnose underlying pituitary abnormalities.…”
Section: Discussionsupporting
confidence: 83%
“…This strongly associates with pituitary adenomas. [781021] Our study supports this data and suggests a simple semiquantitative index to diagnose underlying pituitary abnormalities.…”
Section: Discussionsupporting
confidence: 83%
“…Tc-Sestamibi is significantly lower in P-gp positive meningiomas as compared to P-gp positive intracranial meningiomas and hence it can be used as a marker of P-gp-related MDR [76]. Also based on a small number of patients, it has been concluded that 99m Tc-Sestamibi has the potential to predict P-gp-related MDR in pituitary adenomas [77].…”
Section: Non-glioma Brain Tumors: Ri Of 99mmentioning
confidence: 99%
“…99m Tc − MIBI has not been extensively evaluated in meningiomas and few reports exist. A small-scale study found no correlation between Ki-67 index and tracer uptake; still 99m Tc-MIBI could predict anticancer drug resistance related to the expression of MDR-1 mRNA and its gene product P-gp (Kunishio et al 2003 ). Tumor 99m Tc-TF uptake is not infl uenced by MDR phenotype expression and has been proven suitable for discriminating malignant from benign meningiomas, with an L/N tracer uptake value of 9.6 being the optimal threshold (Fotopoulos et al 2008 ).…”
Section: Assessment Of Meningioma Aggressivenessmentioning
confidence: 99%